Characterization of nickel graphite sealing coatings in the system with the nickel – aluminum bonding coating - Mrdak, Mihailo Rade (Vojnotehnički glasnik / Military Technical Courier, 2013)
This study shows the mechanical and structural characteristics of the Ni - graphite sealing and the effect of their use in parts of the compressors of low and high pressure turbojet engines TV2-117A. Coatings were deposited (APS) atmospheric plasma spray process.Substitution was performed the sealing materials on the working ring compressor , focusing devices compressor and the front body compressor turbojet engines TV2-117A, to ensure maximum air flow temperature of 100 -125 ˚ C through the compressor at a pressure of 7 bara.Soft seals are formed as a double systems consisting of a lower bond layers of   basis on NiAl coatings and sealing of the upper layers of coatings based on Ni - 25% graphite and Ni - 15% graphite.Microstructure of the layers are estimated at the light microscope.Morphology Ni powder particles - graphite and fracture morphology of the coatings was investigated (SEM) Scanning Electron microscope.Microstructural analysis of deposited layers was performed according to standard Pratt-Whitney.Assessment mechanical properties of coatings is done testing microhardness of bond layers method HV0.3 and layers of sealing method macrohardness HR15y. Bond strehgths double coating system of coatings were tested using the tensile breaking. The effect of sealing parts of the compressor was tested in the engine of TV2-117A.   Key words: atmospheric plasma spray (APS),sealing, microstructure, interface, microhardness, macrohardness, bond strength
Keywords: Seals; nickel; Ni; layers; graphite; Engines; Compressors; Coatings; Bonding